IMPROVING COLOSSAL GRID OF 5LP LINTING TECHNOLOGY PROSESSES AND INITIAL IMPROVEMENT (Journal of Science-Innovative Research in Uzbekistan, 2025)
Adjustment of the supply of seed to the linter is performed depending on the density of the seed mass in the working chamber. The performance of the linter on the seed is carried out by changing the length of the chain connecting the variator with the seed density lever in the working chamber and by changing the position of the load on the lever of the density lever.